2017
DOI: 10.5935/1518-0557.20170027
|View full text |Cite
|
Sign up to set email alerts
|

To operate or not to operate on women with deep infiltrating endometriosis (DIE) before in vitro fertilization (IVF)

Abstract: Deep infiltrating endometriosis (DIE) can cause infertility and pelvic pain. There is little evidence of a clear connection between DIE and infertility, and the absolute benefits of surgery for DIE have not been established. This paper aimed to review the current literature on the effect of surgery for DIE on fertility, pregnancy, and IVF outcomes. Clinicians should bear in mind that a comprehensive clinical history is useful to identify patients at risk for endometriosis, although many women remain asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Undoubtedly the management of these patients should be done by a multidisciplinary team. the technique used, it seems that excisional surgery is associated with better spontaneous pregnancy rates in a 9-12 months interval as opposed to ablative surgery 27 . Two randomized control studies of laparoscopic management of endometriomas have demonstrated an increased pregnancy rate when performing cyst wall excision as opposed to cyst wall ablation, with pregnancy rates of 61% versus 23.4% after a two year interval 33 .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Undoubtedly the management of these patients should be done by a multidisciplinary team. the technique used, it seems that excisional surgery is associated with better spontaneous pregnancy rates in a 9-12 months interval as opposed to ablative surgery 27 . Two randomized control studies of laparoscopic management of endometriomas have demonstrated an increased pregnancy rate when performing cyst wall excision as opposed to cyst wall ablation, with pregnancy rates of 61% versus 23.4% after a two year interval 33 .…”
Section: Resultsmentioning
confidence: 97%
“…Th e pregnancy rates were 2.45 times higher in the group of women submitted to surgery before IVF. When DIE is associated with endometriomas, the pregnancy rate is declined furthermore, as compared to DIE alone (82.5% versus 69.4%) 27,34,35 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations